An expanded apolipoprotein D family provides spider mites with dual-layer protection against dietary oxidative stress - Si-Yu Wei; Xin An; Qin-Zhe Sun; Qun Yang; Xi Han; Yu-Fei Shi; Jin-Jun Wang; Jinzhi Niu (Proceedings of the National Academy of Sciences, 2026)
Plant defense has driven the evolution of species-dependent adaptive strategies in many herbivores, but the molecular mechanisms of adaptation in most arthropods remain largely unknown. The two-spotted spider mite ( Tetranychus urticae ) is a generalist herbivore that feeds by sucking the contents of mesophyll cells, a feeding strategy distinct from that of phloem-feeding insects. Here, we show the unexpected differential expression of apolipoprotein D ( ApoD ) genes during feeding when mites are transferred to different host plant species, as well as extreme gene family expansion (64 ApoD paralogs, the largest reported in any organism). We find that ApoD proteins protect mites against reactive oxygen species (ROS) during feeding, and we identify a dual-layer mechanism by which ApoD proteins counteract plant ROS defenses during ingestion and digestion. First, the salivary protein TuApoD2 is secreted during the ingestion of mesophyll cell contents, where it interacts with glycolate oxidase 2 (GOX2) to inhibit H 2 O 2 generation. After ingestion, TuApoD33 in the gut cells also interacts with GOX2 to maintain the inhibition of H 2 O 2 generation. These findings suggest that the evolutionary expansion of the ApoD gene family is a key component of the molecular arms race between herbivorous mites and host plants.